أعلام الشعراء وخصائصهم الفنية واتجاهاتهم الأدبية في ولاية أدماوا بنيجيريا : دراسة تحليلية - عمر، علي فريا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The entry of Islam into West Africa and its penetration into Nigeria are key factors in cultivating Arabic culture in these lands. It has changed the way people think, provided them with other colours of thought and opened the doors of science which is related to Al-Quran and the Hadith until the culture flourished in Adamawa state. There, the world can find scholars who are experts in Arabic culture and religious knowledge. The tendency among scholars to write poetry and prose is among the factors of enthusiasm in the revival of what was eradicated by the British colonials who were abhorrent of the life of the Muslim community who wanted to retain their Arabic and Islamic culture. The scholars of Adamawa created a type of Arabic language poetry based on celestialism and serenity and on accuracy and sweetness in various wonderful ways with beautiful compositions. This study aims to introduce the territory of Adamawa state in Nigeria by examining the role of its scholars and writers in the dissemination of Arabic language and literature. It analyses some of their poems and the artistic and rhetorical methods of poets, by showing their artistic ability and imagination in the formulation of Arabic language poetry. It also addresses their diverse literary orientations by studying the characteristics of some of the trends known in modern Arabic poetry, which indicate their awareness of contemporary Arab poetry. The methods employed were descriptive, inductive and analytical approaches in analyzing, collecting and describing their poetry by defining its purpose and subjects. The artistic values of the poetry were also extracted, interpreted and analyzed against the various literary trends. The research has concluded several results. The most important of these is that the state of Adamawa has many well known poets. The research also highlights their poetic talents and revives their many literary productions, which many researchers and readers do not know, the link between them and writers in the Islamic world and their enthusiasm and courage in the preservation of Arabic and Islamic culture. This enabled them to become famous poets in Nigeria.